Characterization of moisture states and transport in MUF resin-impregnated poplar wood using low field nuclear magnetic resonance. Issue 6 (31st March 2021) - Xu, Kang; Yuan, Shaofei; Gao, Yulei; Wu, Yiqiang; Zhang, Jian; Li, Xianjun; Lu, Jianxiong
Abstract: In this study, the spin–spin relaxation time ( T 2 ) distributions of free water and bound water, as well as the moisture content (MC) profiles of MUF resin-impregnated poplar wood ( Populous tomentosa ) sample ( RI ) were investigated by low-field nuclear magnetic resonance, with the aim of providing insights into how MUF resin impregnation affects the moisture states and moisture transport in modified poplar wood during drying. The T 2 curves demonstrated that the resin treatment did not increase the number of peaks in the T 2 distributions, but affected the T 2 value as compared to the control. Above the fiber saturation point (FSP), the T 22 (corresponds to the free water in wood rays and wood fibers) of the RI sample exhibited an increase compared to the control, while the T 23 (corresponds to the free water in the vessels) was almost unchanged. Below the FSP, a shorter T 21 (corresponding to the bound water) of the RI sample was observed compared to the control. The drying curves and MC profiles indicated a significant difference in the moisture transport in the RI sample as compared to the control. The gradually cured resin system in the wood surface layer during drying provided a barrier for the transfer of water in the center layer toward to the surface, causing the resin curing reactions in the surface and core layers to be out of sync. Therefore, a more significant MC gradient was observed for the resin-impregnated sample.